Chronic ischaemia does not appear to hinder healing with Integra®: implementation at a tibial artery bypass site1. Issue 5 (14th January 2015) - Michot, Audrey; Chaput, Benoit; Gobel, Fabienne; Menez, Tiphaine; de Bonnecaze, Guillaume; Pelissier, Philippe
Abstract: Wounds with exposed vessels, especially in artery bypass procedures, can pose a barrier to adequate skin healing. Skin grafts or flaps are sometimes difficult to perform in the face of the ischaemia that is often present in such cases. We report a case of a 73‐year‐old man who presented with grade IV peripheral arterial disease necessitating salvage of the lower limb using artery bypass surgery. Immediate exposure of femorotibial artery secondary to skin necrosis following the bypass led us to propose an innovative means of wound coverage using Integra ®, a well‐known dermal regeneration template. The wound healed uneventfully with an appearance similar to that of the adjacent skin. Integra ® seems to be less demanding in terms of the vascular wound bed and the degree of oxygenation than a conventional skin graft. This finding could support further indications for this dermal regeneration template.